The Effect Of Original Local Government Revenue, Intergovernmental Revenue, And Capital Expenditures Toward Financial Performance Of Regency And Municipal Goverments In The Province Of West Java Fiscal Year 2016-2020 - Andi Muhammad Sadli; Rakhmat; Ida Farida (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
The aims of this research to know the impact of: 1) Original Local Government Revenues to Financial Performance of Regency and Municipal Goverments in the Province of West Java. 2) Intergovernmental Revenue to Financial Performance of Regency and Municipal Goverments in the Province of West Java. 3) Capital Expenditures to Financial Performance of Regency and Municipal Goverments in the Province of West Java. 4) Original Local Government Revenues, Intergovernmental Revenue, and Capital Expenditures to Financial Performance of Regency and Municipal Goverments in the Province of West Java. The subject in this research is regency and municipality in the Province from West Java. The data used comes from Realization Report of APBD fiscal years 2016-2020. The technic of data collection are using documentation method. Pre-paid test analysis is using assumption classic test. The hypothesis test of this research is using simple linear regression analysis and multiple linear regression analysis. The result of the research shows that:1) There are positive and significant effect of Original Local Government Revenue Financial (X1) to Local Government Financial Performance (Y). It showed by correlation coefficient (rx1y) = 0,212, determination coefficient (r2x1y) = 0,045, and t arithmetic 2,501> t table 1,97769. 2) There are positive effect however it not significant of Intergovernmental Revenue (X2) to Local Government Financial Performance (Y). It showed by correlation coefficient (rx2y) = 0,206, determination coefficient (r2x2y) = 0,042, and t arithmetic 2,427> t table 1,97769. 3) There are negative and significant effect of Capital Expenditure (X3) Local Government Financial Performance (Y). It showed by correlation coefficient (rx3y) = -0,182, determination coefficient (r2x3y) =0,033, and t arithmetic -2,134 t table 1,97769. 4) There are positive effect of Original Local Government Revenue Financial (X1) and Intergovernmental Revenue (X2), and negative effect of Capital Expenditure (X3) to Local Government Financial Performance (Y) It showed correlation coefficient (Ry(1,2,3) = 0,332, determination coefficient (R2y(1,2,3) = 0,110 and F aritmetic 5,420 > F table 2,67.